2014
DOI: 10.1177/0734282914546287
|View full text |Cite
|
Sign up to set email alerts
|

Motivation and Engagement in the United States, Canada, United Kingdom, Australia, and China

Abstract: This study explored motivation and engagement among North American (the United States and Canada; n = 1,540), U.K. (n = 1,558), Australian (n = 2,283), and Chinese (n = 3,753) secondary school students. Motivation and engagement were assessed via students’ responses to the Motivation and Engagement Scale–High School (MES–HS). Confirmatory factor analysis using Mplus found good fit for each of the four samples. Multi-group invariance tests demonstrated comparable factor structure, reliability, distributional pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 23 publications
3
26
1
3
Order By: Relevance
“…Research on cross-national comparisons is increasing (Martin, Yu, Papworth, Ginns, & Collie, 2015), and with an increase, constructs, such as test anxiety, need to be assessed to determine psychometric equivalency prior to examining differences across nations (Putnick & Bornstein, 2016). In the current study, test anxiety as measured by the TAM-C was found to be psychometrically equivalent across countries and genders, and country and gender differences were noted, with U.K. undergraduate students and females reporting higher levels of test anxiety than U.S. undergraduate students and males.…”
Section: Resultsmentioning
confidence: 99%
“…Research on cross-national comparisons is increasing (Martin, Yu, Papworth, Ginns, & Collie, 2015), and with an increase, constructs, such as test anxiety, need to be assessed to determine psychometric equivalency prior to examining differences across nations (Putnick & Bornstein, 2016). In the current study, test anxiety as measured by the TAM-C was found to be psychometrically equivalent across countries and genders, and country and gender differences were noted, with U.K. undergraduate students and females reporting higher levels of test anxiety than U.S. undergraduate students and males.…”
Section: Resultsmentioning
confidence: 99%
“…This is a groupadministered 44-item scale measuring adaptive cognitions (self-belief, valuing, learning focus), adaptive behaviours (planning, task management, persistence), impeding/maladaptive cognitions (anxiety, failure avoidance, uncertain control), and maladaptive behaviours (selfsabotage and disengagement) (Martin, 2010). Data collected using this scale has demonstrated good reliability and validity (Martin, 2007;Martin, Yu, Papworth, Ginns & Collie, 2015) and has been used in a wide programme of research studies, demonstrating correlates with school enjoyment, classroom participation and educational aspirations (Martin, 2007).…”
Section: Academic Motivation and Engagement Scale (High School)mentioning
confidence: 99%
“…SDT kontekste atlikti tyrimai rodo, kad autonominė akademinė motyvacija siejasi su daugeliu pageidautinų akademinių pasekmių, pavyzdžiui, geresniu lankomumu, kūrybiškumu, akademiniu pažangumu ir t. t. (Maurer, Allen, Gatch, Shankar, & Sturges, 2013;Vasteenkiste et al, 2006). Remdamiesi tiek teorinėmis prielaidomis (Vansteenkiste et al, 2006), tiek empiriniais tyrimais (Fortier, Vallerand, & Guay, 1995), keliame hipotezę, kad jei sukurta skalė yra validi (turimas omenyje kriterinis laike sutampantis validumas), bus gautos teigiamos sąsajos tarp autonominių motyvacijos tipų ir semestro vidurkio bei pasitenkinimo studijuojamu dalyku, ir atvirkščiai -tikėtinos sąsajos tarp šių konstruktų ir amotyvacijosneigiamos (hipotezė H2).…”
Section: • Išorinė Motyvacijaunclassified
“…Taip pat nustatyta, kad introjekcinė motyvacija su pasitenkinimu studijų programa siejasi silpnai neigiamai, galbūt dėl to, kad introjekcinė motyvacija atspindi neigiamas emocijas (Vallerand & Ratelle, 2002), o nepasitenkinimas studijomis taip pat turi neigiamų emocijų atspalvį. Taigi, šie rezultatai iš esmės atitinka kitų autorių gautus rezultatus, kurie rodo, kad vidinė motyvacija ir autonomiškesni išorinės motyvacijos tipai teigiamai siejasi su pozityviomis akademinėmis pasekmėmis (Maurer et al, 2013;Vansteenkiste et al, 2006;. Tikrinant H3 hipotezę, buvo tiriamas SAMS-21 konvergentinis ir divergentinis validumas.…”
Section: Rezultatų Aptarimasunclassified